(untitled) (Research, Society and Development, 2025)
We report in this manuscript a literature review aimed at analyzing the concept of alterity used in research within the fields of Psychology and Education. In this endeavor, we reflect on the implications of the popularization of ways of interpreting disability for the lives of those who experience it. Historically, we have observed that many of these interpretations have given rise to frameworks that still sustain practices of exclusion and the silencing of differences in educational settings. We highlight gaps in the regulatory documents of pedagogical proposals for inclusion regarding the focus on communicative processes, understood as a necessary theoretical and methodological parameter for appropriately addressing human diversity and promoting social justice in educational contexts. Based on this premise, we focused on conceptions of alterity used in research that investigates interaction and communication with people who live with some form of disability. The objective of this review was to identify the characteristics of the concept of alterity and to highlight methodological approaches for investigating this phenomenon, as well as the implications of the knowledge produced for educational practices. Our expectation was to reaffirm the potential of alterity to foster the ethical exercise of communication in educational settings.Searches for articles were carried out in the SciELO, CAPES Journals Portal, and PePSIC databases. After applying inclusion and exclusion criteria, we selected ten articles considered the most relevant. In analyzing these texts, we observed different nuances in the concept of alterity—sometimes reproducing exclusionary logics, and at other times proposing encounters grounded in listening and the practice of ethics. In conclusion, we argue for the appropriation of the definition of alterity as a process mediated by language.